Does counting change what is counted? Potential for paradigm change through performance metrics. Issue 1 (16th November 2018) - Sætnan, Ann Rudinow; Tøndel, Gunhild; Rasmussen, Bente
Abstract: This qualitative case study of emergent practices in a multi-paradigmatic field at one department in Norway explores how performance metrics in science intra-act with staff composition and resource allocation, potentially affecting paradigm trends. Inspired by agential realism, we discuss four key metrics as the material core of an assemblage through which Academe is iteratively enacted. Separately, together, and in concert with other metrics and practices, these play major roles in steering disciplinary development. Our empirical material consists of official documents, bibliometric outputs, and auto-ethnographic observations. Metrics and the practices and institutions they measure are iteratively co-emergent. Responses to the assemblage include hyper-cooperation, cooptation, and resistance. Effects are not uniform and may add to discrimination according to field and position status. Emphasis on international publication may also lead to increasing distance between social sciences and the local society they are entrusted to study. Recently, we and other colleagues have become concerned that performance metrics may also be contributing to paradigm bias in hiring procedures.